RESPON MASYARAKAT DAN PEMERINTAH DAERAH TERHADAP PERTUMBUHAN TEMPAT IBADAT (Studi Kasus Penutupan Ruko dan Rumah Tinggal yang Digunakan sebagai Tempat Ibadat Umat Kristen di Cianjur Jawa Barat) - Ibnu Hasan Muchtar (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This study employs qualitative approach that aims to find out the facts about the closing of seven churches conducted by Cianjur government and it evokes some reactions from Cianjur church organization (BKSAG) by reporting that case to national comission on human rights (Komnas HAM). The study shows that the church is not the real church like the ideal church but the shopping building and houses as residential areas are used as worship houses. Those churches are banned and closed by civil service police unit (Satpol PP) because they do not have a building permit. This study also explores the different understanding on PBM 2006 about the requirements to build worship houses and late local government response to that case that occurs for long time.